Resolutions and Decisions of the Economic and Social Council: 2021 Session - United Nations (United Nations)
These are the Official Records of the Resolutions and Decisions of the Economic and Social Council for Organizational and Resumed Organizational and Substantive and Resumed Substantive Sessions of 2021. The UN Economic and Social Council (ECOSOC) discusses global economic, social and environmental challenges. It coordinates the related work of UN entities and regional commissions, as well as of its subsidiary bodies, particularly its functional commissions. Its annual, month-long substantive session in July is held in alternate years in New York and Geneva.